An “Occult” Popliteal Vein Aneurysm Causing Pulmonary Embolism - Oladiran, Adedapo; Maharaj, Dale; Ariyanayagam, Dinesh; Darling, Ralph Clement, III (International Journal of Angiology, 2021)
Popliteal vein aneurysm (PVAs), though uncommon, can be a cause of pulmonary emboli. They can also result in pulmonary vein embolism despite the use of anticoagulation therapy. We report the case of an otherwise fit, 64-year-old male who had a history of sudden onset of dyspnea on exercise with near syncope. A computed tomography pulmonary angiogram confirmed filling defects in the lung bases in keeping with pulmonary emboli. He was anticoagulated and a venous duplex scan revealed a fusiform suprageniculate PVA with no evidence of thrombus in the lumen. He underwent resection of the aneurysm with lateral vein patch graft repair and was placed on anticoagulation for 6 months with no recurrence after 2 years of follow-up. PVAs are rare and can either be symptomatic or asymptomatic. We advise early surgical treatment to prevent the significant morbidity and mortality associated with thromboembolization. Written consent was obtained from the patient for publication of case and use of images.
Keywords: popliteal vein; pulmonary angiogram; aneurysm; venogram